2020
DOI: 10.1007/978-3-030-64861-9_50
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Public Service Experience on Adopting Digital Government Innovations in Ethiopia

Abstract: Digital government innovation is being recognised as a solution to many problems faced by governments in providing services to their citizens. It is especially important for lowincome countries where there are resource constraints. This research was aimed at exploring the moderating effect of gender on the adoption of a digital government innovation in Ethiopia based on the UTAUT model (n=270) and using structural equation modeling (SEM). The results reveal that gender only moderates the relationship between f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…Finally, the finding of this study shows that the relationship between facilitating condition and behavioral intention to use patient portal were positively moderated by gender. This implied that the availability of resource, infrastructure support and knowledge has higher impact on female than male to intend to use patient portal, which is the effect of facilitating condition on behavioral intention to use the patient portal is stronger in female also this result supported by other studies (96). The possible reason for this significant difference might be the gender digital divide.…”
Section: Discussionsupporting
confidence: 58%
“…Finally, the finding of this study shows that the relationship between facilitating condition and behavioral intention to use patient portal were positively moderated by gender. This implied that the availability of resource, infrastructure support and knowledge has higher impact on female than male to intend to use patient portal, which is the effect of facilitating condition on behavioral intention to use the patient portal is stronger in female also this result supported by other studies (96). The possible reason for this significant difference might be the gender digital divide.…”
Section: Discussionsupporting
confidence: 58%
“…It is possible that through training and specialized courses, more knowledge could be gained about the importance and necessity of implementing artificial intelligence (Senshaw and Twinomurinzi, 2021). Government institutions should offer free courses for workers to learn more about AI, allowing them to become more familiar with and adapt to new trends, especially those who are more reluctant, since the implementation of this model will also allow for good governance and greater transparency.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also validated and supported the findings that performance expectancy is the most significant determinant of technology adoption due to anticipated perceived benefits from such technology for their performance [167][168][169]. On the contrary, other researchers have shown that performance expectancy does not necessarily influence the adoption of technology (m-government) [170].…”
Section: Discussionmentioning
confidence: 85%
“…e ease of use of any technology [172][173][174]. Few studies have however demonstrated that the extent of ease of use (effort expectancy) of technology does not influence its acceptance [170,175,176]. e nondirect effect of effect expectancy on the technology adoption can be attributed to people's over familiarization with new technologies (mobile) which make them well acquainted with such technologies, and thus the issue of ease of use does not arise.…”
Section: Discussionmentioning
confidence: 99%